Modular linear optical circuits - Mennea, P; Clements, W; Smith, D; Gates, J; Metcalf, B; Bannerman, R; Burgwal, R; Renema, J; Kolthammer, W; Walmsley, I; Smith, P (Optical Society of America, 2018)
Linear optical circuits that can provide reconfig- urable interference between several optical modes are emerging as a powerful tool for both classical and quantum optics. In this work, we propose and demonstrate a modular architecture for building these circuits. Each module contains independent phase-controlled Mach-Zehnder interferometers, and several modules can be interfaced to build large reconfigurable interferometers. We demonstrate our approach by fabricating three modules in the form of UV-written silica-on-silicon chips. We characterize these chips, connect them to each other, and implement a wide range of linear optical transformations. Our work facilitates the development of large scale linear optical circuits for quantum optics.